(3QSGdI aj eGgjI GdLOQi hJOHjQg EPG hbYs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s
(3ChdgG (B:s
(3bGd bUOfG ai gPg GdebGdI gh Cf fHjf eGgjI GdLOQi hMbjbJgG hce CUfGagG heG UaI cd hGMO efgG s
(3BNQgG (B:s
(3Ch jOb GdJeQ hSef GdHbQ hJTO Ydjg aEf gPg jdjf hjQVi GdLdO ajSgd NQhLg hjScf GdhLY HEPf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3jdjg YOI ahGFOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs